Low-shrinkage antistatic PBT material for loose tube and its preparation method

CN123004098APending Publication Date: 2026-10-30YANGZHOU JINSEN OPTOELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611388624.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]综上所述,松套管的收缩与静电缺陷虽表现形式不同,前者源于材料的热力学特性,后者起因于电荷的物理积累,但两者最终都指向对光纤微弯损耗和余长控制的破坏,其解决思路也殊途同归-均需依赖于对高分子材料科学的深入理解、精密的生产工艺调控以及功能性助剂的合理应用,任何单一环节的疏忽都可能演变为光缆长期运行中的质量隐患

Benefits of technology

[0016]本发明的有益效果:本发明制备的PBT料适合用于松套管,具有低收缩抗静电的优点。PBT料组分中二[4-(1,1-二甲基乙基)苯甲酰-氧]氢氧化铝和聚乙烯基环戊烷的组合使用,提高了材料的抗收缩性能,甲基三羟乙基甲基硫酸铵和非离子型抗静电剂组合使用,提高了材料的抗静电性能,且协同增效。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The application discloses a kind of low shrinkage antistatic PBT material for loose sleeve and a preparation method thereof.The PBT material is prepared from the following components by weight ratio: polybutylene terephthalate 100-200 parts, flame retardant 30-50 parts, nucleating agent 0.5-1.5 parts, antistatic agent 2-8 parts, lubricant 1-3 parts.The PBT material prepared by the application is suitable for loose sleeve and has the advantages of low shrinkage and antistatic property.The combination of di[4-(1,1-dimethyl ethyl) benzoyl-oxygen] aluminum hydroxide and polyvinyl cyclopentane in the PBT material components improves the shrinkage resistance of the material, and the combination of methyl trihydroxyethyl methyl ammonium sulfate and non-ionic antistatic agent improves the antistatic property of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of optical cable technology, specifically relating to a low-shrinkage, antistatic PBT material for loose tubes and its preparation method. Background Technology

[0002] As the core component in optical cables that houses optical fibers, loose tubes face two major defects during production and use: shrinkage and static electricity. These are key factors affecting the long-term reliability and transmission performance of optical cables.

[0003] The shrinkage phenomenon of loose tubes is essentially the result of the combined effects of internal stress release and thermal motion of polymer chain segments. Its causes are complex and span the entire lifecycle of optical cables, from material selection and extrusion processes to service life. From a material properties perspective, loose tube substrates, represented by polybutylene terephthalate (PBT), have their molecular chains forcibly oriented and stretched during extrusion molding, resulting in the storage of significant internal stress. When subsequently affected by temperature changes, the molecular chains revert to a more stable coiled state, macroscopically manifesting as shrinkage of the tube's dimensions. Experimental data shows that after a temperature cycle from +60℃ to -60℃, the shrinkage rate of PBT loose tubes can fluctuate significantly between -1.4‰ and 7.8‰, with particularly pronounced shrinkage in low-temperature regions (such as -40℃). This directly confirms that temperature is a key external factor inducing shrinkage. If this shrinkage is uncontrolled, it can easily lead to fiber bending, increasing transmission loss and even causing communication interruptions. At the process control level, the "excess length" of the optical fiber within the loose tube—that is, the excess length of the optical fiber relative to the tube length—is directly coupled with post-shrinkage. The speed of the tube forming production line, the temperature difference in the cooling water tank, and the crystallinity of the PBT material itself all affect the cooling and shrinkage behavior of the tube, thereby altering the excess fiber length. For example, excessively high production line speeds can lead to insufficient cooling of the tube, resulting in increased post-shrinkage and uncontrollable changes in the excess fiber length. To address this persistent defect, the industry has explored solutions from both material and process perspectives. In terms of material modification, adjusting the crystallinity and rheological properties of PBT through blending modification (such as adding polypropylene or compatibilizers), or employing novel compression processes to forcibly offset shrinkage stress, can effectively reduce post-shrinkage to near-zero levels.

[0004] Another major challenge alongside shrinkage defects is the increasingly prominent electrostatic adsorption problem in all-dry loose tube structures. Because traditional grease fillers have been replaced by water-blocking powder or yarn, the excellent insulation of plastic loose tubes makes it difficult to release static charges. The resulting static electricity strongly attracts optical fibers or water-blocking elements inside the tube, causing fiber adhesion to the wall, accumulation, and uneven excess length distribution, and introducing additional transmission losses due to increased frictional resistance. To eliminate this electrostatic hazard, the most direct strategy in practice is to introduce antistatic components into the loose tube material formulation, such as adding conductive fillers like graphite powder or graphene, or specialized antistatic agents. Simultaneously, a lubricant (such as silicone) is added to reduce friction between the optical fiber and the tube wall, thus ensuring the free movement of the optical fiber within the tube and the stability of its excess length.

[0005] In summary, although the shrinkage of loose tubes and electrostatic defects manifest differently—the former stemming from the thermodynamic properties of materials and the latter from the physical accumulation of charge—both ultimately lead to the destruction of fiber microbending loss and excess length control. The solutions also converge on the same point: a deep understanding of polymer materials science, precise control of production processes, and the rational application of functional additives are all essential. Neglecting any single link can potentially lead to quality hazards in the long-term operation of the optical cable. Summary of the Invention

[0006] The purpose of this invention is to provide a low-shrinkage, antistatic PBT material for loose-sleeve tubing and its preparation method.

[0007] A low-shrinkage, antistatic PBT material for loose tubing is made from the following components in parts by weight: 100-200 parts of polybutylene terephthalate, 30-50 parts of flame retardant, 0.5-1.5 parts of nucleating agent, 2-8 parts of antistatic agent, and 1-3 parts of lubricant.

[0008] The viscosity of the polybutylene terephthalate is 0.75-0.88.

[0009] The flame retardant is one or more of aluminum hydroxide, zinc borate, ammonium polyphosphate, triphenyl phosphate, and melamine cyanurate.

[0010] The nucleating agent is a mixture of bis[4-(1,1-dimethylethyl)benzoyl-oxy]aluminum hydroxide (CAS No.: 13170-05-3) and polyvinylcyclopentane in a mass ratio of (1-3):1.

[0011] The antistatic agent is a mixture of methyltrihydroxyethylmethylammonium sulfate and nonionic antistatic agents in a mass ratio of 1:(1-3).

[0012] The preparation method of the nonionic antistatic agent is as follows: pentaerythritol stearate and tristearate are put into a reaction vessel, nitrogen is introduced to control the negative pressure at 0.02-0.06 MPa, the temperature is raised to 120-140℃, and the reaction is carried out under stirring for 30-50 min, and then the temperature is lowered to 100-110℃ to obtain the nonionic antistatic agent; the weight ratio of tristearate to pentaerythritol stearate is (2-5):1.

[0013] The lubricant is one or more of stearic acid, calcium stearate, zinc stearate, and paraffin.

[0014] The preparation method of the low-shrinkage antistatic loose tube PBT material is carried out according to the following steps: polybutylene terephthalate, flame retardant, nucleating agent, antistatic agent and lubricant are added to a high-speed mixer and mixed at a speed of 2500-3000 rpm / min for 5-10 minutes. After stirring evenly, the mixture is discharged to obtain a mixture. The mixture is then melted, extruded and granulated through a twin-screw extruder to obtain PBT material.

[0015] The parameters of the extrusion preparation process are as follows: screw speed: 50-100 r / min; temperature settings: first temperature zone: 170-190℃; second temperature zone: 200-210℃; third temperature zone: 210-220℃; fourth temperature zone: 200-210℃; fifth temperature zone: 190-200℃; sixth temperature zone: 190-200℃; die temperature: 220-240℃.

[0016] The beneficial effects of this invention are as follows: The PBT material prepared by this invention is suitable for use in loose-sleeve tubing and has the advantages of low shrinkage and antistatic properties. The combined use of bis[4-(1,1-dimethylethyl)benzoyl-oxy]aluminum hydroxide and polyvinylcyclopentane in the PBT material composition improves the material's anti-shrinkage performance, while the combined use of methyltrihydroxyethylmethylammonium sulfate and nonionic antistatic agents improves the material's antistatic performance, with synergistic effects. Detailed Implementation

[0017] To facilitate understanding of the present invention, a more comprehensive description will be given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.

[0018] Example 1 A low-shrinkage, antistatic PBT material for loose-sleeve tubing is composed of the following components in parts by weight: 160 parts polybutylene terephthalate (PBT), 40 parts aluminum hydroxide, 1 part nucleating agent, 6 parts antistatic agent, and 2 parts calcium stearate. The PBT has a viscosity of 0.82. The nucleating agent is a mixture of bis[4-(1,1-dimethylethyl)benzoyl-oxy]aluminum hydroxide (CAS No.: 13170-05-3) and polyvinylcyclopentane in a mass ratio of 2:1. The antistatic agent is a mixture of methyltrihydroxyethylmethylammonium sulfate and a nonionic antistatic agent in a mass ratio of 1:2.

[0019] The preparation method of the nonionic antistatic agent is as follows: pentaerythritol stearate and tristearate are added to a reaction vessel, nitrogen is introduced to control the negative pressure at 0.04 MPa, the temperature is raised to 130°C, and the reaction is carried out under stirring for 40 min, and then the temperature is lowered to 105°C to obtain the nonionic antistatic agent; the weight ratio of tristearate to pentaerythritol stearate is 3:1.

[0020] The preparation method of the low-shrinkage antistatic loose tube PBT material is carried out according to the following steps: polybutylene terephthalate, aluminum hydroxide, nucleating agent, antistatic agent and calcium stearate are added to a high-speed mixer and mixed at a speed of 2800 rpm / min for 8 minutes. After stirring evenly, the mixture is discharged to obtain a mixture. The mixture is melted, extruded and granulated through a twin-screw extruder to obtain PBT material.

[0021] The parameters of the extrusion preparation process are as follows: screw speed: 80 r / min; temperature settings: first temperature zone: 180℃; second temperature zone: 205℃; third temperature zone: 215℃; fourth temperature zone: 205℃; fifth temperature zone: 195℃; sixth temperature zone: 195℃; die temperature: 230℃.

[0022] Example 2 A low-shrinkage, antistatic PBT material for loose-sleeve tubing is composed of the following components in parts by weight: 110 parts polybutylene terephthalate, 32 parts zinc borate, 0.6 parts nucleating agent, 3 parts antistatic agent, and 1 part stearic acid. The polybutylene terephthalate has a viscosity of 0.78. The nucleating agent is a mixture of bis[4-(1,1-dimethylethyl)benzoyl-oxy]aluminum hydroxide (CAS No.: 13170-05-3) and polyvinylcyclopentane in a 1:1 mass ratio. The antistatic agent is a mixture of methyltrihydroxyethylmethylammonium sulfate and a nonionic antistatic agent in a 1:1 mass ratio.

[0023] The preparation method of the nonionic antistatic agent is as follows: pentaerythritol stearate and tristearate are added to a reaction vessel, nitrogen is introduced to control the negative pressure at 0.03 MPa, the temperature is raised to 125°C, and the reaction is carried out under stirring for 35 minutes, and then the temperature is lowered to 100°C to obtain the nonionic antistatic agent; the weight ratio of tristearate to pentaerythritol stearate is 2:1.

[0024] The preparation method of the low-shrinkage antistatic loose tube PBT material is carried out according to the following steps: polybutylene terephthalate, zinc borate, nucleating agent, antistatic agent and stearic acid are added to a high-speed mixer and mixed at a speed of 2500 rpm / min for 10 min. After stirring evenly, the mixture is discharged to obtain a mixture. The mixture is melted, extruded and granulated through a twin-screw extruder to obtain PBT material.

[0025] The parameters of the extrusion preparation process are as follows: screw speed: 60 r / min; temperature settings: first temperature zone: 170℃; second temperature zone: 200℃; third temperature zone: 210℃; fourth temperature zone: 200℃; fifth temperature zone: 190℃; sixth temperature zone: 190℃; die temperature: 220℃.

[0026] Example 3 A low-shrinkage, antistatic PBT material for loose-sleeve tubing is composed of the following components in parts by weight: 190 parts polybutylene terephthalate (PBT), 45 parts triphenyl phosphate (TPP), 1.2 parts nucleating agent, 7 parts antistatic agent, and 3 parts paraffin wax. The PBT has a viscosity of 0.86. The nucleating agent is a mixture of bis[4-(1,1-dimethylethyl)benzoyl-oxy]aluminum hydroxide (CAS No.: 13170-05-3) and polyvinylcyclopentane in a mass ratio of 3:1. The antistatic agent is a mixture of methyltrihydroxyethylmethylammonium sulfate and a nonionic antistatic agent in a mass ratio of 1:3.

[0027] The preparation method of the nonionic antistatic agent is as follows: pentaerythritol stearate and tristearate are added to a reaction vessel, nitrogen is introduced to control the negative pressure at 0.06 MPa, the temperature is raised to 140°C, and the reaction is carried out under stirring for 50 min, and then the temperature is lowered to 110°C to obtain the nonionic antistatic agent; the weight ratio of tristearate to pentaerythritol stearate is 4:1.

[0028] The preparation method of the low-shrinkage antistatic loose tube PBT material is carried out according to the following steps: polybutylene terephthalate, triphenyl phosphate, nucleating agent, antistatic agent and paraffin are added to a high-speed mixer and mixed at a speed of 3000 rpm / min for 6 min. After stirring evenly, the mixture is discharged to obtain a mixture. The mixture is melted, extruded and granulated through a twin-screw extruder to obtain PBT material.

[0029] The parameters of the extrusion preparation process are as follows: screw speed: 100 r / min; temperature settings: first temperature zone: 190℃; second temperature zone: 210℃; third temperature zone: 220℃; fourth temperature zone: 210℃; fifth temperature zone: 200℃; sixth temperature zone: 200℃; die temperature: 240℃.

[0030] Comparative Example 1 A low-shrinkage, antistatic PBT material for loose-sleeve tubing is made from the following components in parts by weight: 160 parts polybutylene terephthalate, 40 parts aluminum hydroxide, 1 part bis[4-(1,1-dimethylethyl)benzoyl-oxy]aluminum hydroxide, 6 parts antistatic agent, and 2 parts calcium stearate. The polybutylene terephthalate has a viscosity of 0.82. The antistatic agent is a mixture of methyltrihydroxyethyl methyl ammonium sulfate and a nonionic antistatic agent in a mass ratio of 1:2.

[0031] The preparation method of the nonionic antistatic agent is as follows: pentaerythritol stearate and tristearate are added to a reaction vessel, nitrogen is introduced to control the negative pressure at 0.04 MPa, the temperature is raised to 130°C, and the reaction is carried out under stirring for 40 min, and then the temperature is lowered to 105°C to obtain the nonionic antistatic agent; the weight ratio of tristearate to pentaerythritol stearate is 3:1.

[0032] The preparation method of the low-shrinkage antistatic loose tube PBT material is carried out according to the following steps: polybutylene terephthalate, aluminum hydroxide, bis[4-(1,1-dimethylethyl)benzoyl-oxy]aluminum hydroxide, antistatic agent, and calcium stearate are added to a high-speed mixer and mixed at a speed of 2800 rpm / min for 8 min. After stirring evenly, the mixture is discharged to obtain a mixture. The mixture is then melted, extruded, and granulated through a twin-screw extruder to obtain PBT material.

[0033] The parameters of the extrusion preparation process are as follows: screw speed: 80 r / min; temperature settings: first temperature zone: 180℃; second temperature zone: 205℃; third temperature zone: 215℃; fourth temperature zone: 205℃; fifth temperature zone: 195℃; sixth temperature zone: 195℃; die temperature: 230℃.

[0034] Comparative Example 2 A low-shrinkage, antistatic PBT material for loose-sleeve tubing is made from the following components in parts by weight: 160 parts polybutylene terephthalate, 40 parts aluminum hydroxide, 1 part polyvinylcyclopentane, 6 parts antistatic agent, and 2 parts calcium stearate. The polybutylene terephthalate has a viscosity of 0.82. The antistatic agent is a mixture of methyltriethylmethylammonium sulfate and a nonionic antistatic agent in a mass ratio of 1:2.

[0035] The preparation method of the nonionic antistatic agent is as follows: pentaerythritol stearate and tristearate are added to a reaction vessel, nitrogen is introduced to control the negative pressure at 0.04 MPa, the temperature is raised to 130°C, and the reaction is carried out under stirring for 40 min, and then the temperature is lowered to 105°C to obtain the nonionic antistatic agent; the weight ratio of tristearate to pentaerythritol stearate is 3:1.

[0036] The preparation method of the low-shrinkage antistatic loose tube PBT material is carried out according to the following steps: polybutylene terephthalate, aluminum hydroxide, polyvinylcyclopentane, antistatic agent, and calcium stearate are added to a high-speed mixer and mixed at a speed of 2800 rpm / min for 8 minutes. After stirring evenly, the mixture is discharged to obtain a mixture. The mixture is then melted, extruded, and granulated through a twin-screw extruder to obtain PBT material.

[0037] The parameters of the extrusion preparation process are as follows: screw speed: 80 r / min; temperature settings: first temperature zone: 180℃; second temperature zone: 205℃; third temperature zone: 215℃; fourth temperature zone: 205℃; fifth temperature zone: 195℃; sixth temperature zone: 195℃; die temperature: 230℃.

[0038] Comparative Example 3 A low-shrinkage, antistatic PBT material for loose-sleeve tubing is made from the following components in parts by weight: 160 parts polybutylene terephthalate, 40 parts aluminum hydroxide, 1 part nucleating agent, 6 parts methyltrihydroxyethylmethylammonium sulfate, and 2 parts calcium stearate. The viscosity of the polybutylene terephthalate is 0.82. The nucleating agent is a mixture of bis[4-(1,1-dimethylethyl)benzoyl-oxy]aluminum hydroxide (CAS No.: 13170-05-3) and polyvinylcyclopentane in a mass ratio of 2:1.

[0039] The preparation method of the low-shrinkage antistatic loose tube PBT material is carried out according to the following steps: polybutylene terephthalate, aluminum hydroxide, nucleating agent, methyltrihydroxyethyl methyl ammonium sulfate, and calcium stearate are added to a high-speed mixer and mixed at a speed of 2800 rpm / min for 8 minutes. After stirring evenly, the mixture is discharged to obtain a mixture. The mixture is then melted, extruded, and granulated through a twin-screw extruder to obtain PBT material.

[0040] The parameters of the extrusion preparation process are as follows: screw speed: 80 r / min; temperature settings: first temperature zone: 180℃; second temperature zone: 205℃; third temperature zone: 215℃; fourth temperature zone: 205℃; fifth temperature zone: 195℃; sixth temperature zone: 195℃; die temperature: 230℃.

[0041] Comparative Example 4 A low-shrinkage, antistatic PBT material for loose-sleeve tubing is made from the following components in parts by weight: 160 parts polybutylene terephthalate, 40 parts aluminum hydroxide, 1 part nonionic antistatic agent, 6 parts antistatic agent, and 2 parts calcium stearate. The viscosity of the polybutylene terephthalate is 0.82. The nucleating agent is a mixture of bis[4-(1,1-dimethylethyl)benzoyl-oxy]aluminum hydroxide (CAS No.: 13170-05-3) and polyvinylcyclopentane in a mass ratio of 2:1.

[0042] The preparation method of the nonionic antistatic agent is as follows: pentaerythritol stearate and tristearate are added to a reaction vessel, nitrogen is introduced to control the negative pressure at 0.04 MPa, the temperature is raised to 130°C, and the reaction is carried out under stirring for 40 min, and then the temperature is lowered to 105°C to obtain the nonionic antistatic agent; the weight ratio of tristearate to pentaerythritol stearate is 3:1.

[0043] The preparation method of the low-shrinkage antistatic loose tube PBT material is carried out according to the following steps: polybutylene terephthalate, aluminum hydroxide, nucleating agent, nonionic antistatic agent, and calcium stearate are added to a high-speed mixer and mixed at a speed of 2800 rpm / min for 8 minutes. After stirring evenly, the mixture is discharged to obtain a mixture. The mixture is then melted, extruded, and granulated through a twin-screw extruder to obtain PBT material.

[0044] The parameters of the extrusion preparation process are as follows: screw speed: 80 r / min; temperature settings: first temperature zone: 180℃; second temperature zone: 205℃; third temperature zone: 215℃; fourth temperature zone: 205℃; fifth temperature zone: 195℃; sixth temperature zone: 195℃; die temperature: 230℃.

[0045] Experimental example: Shrinkage performance test: The molding shrinkage rate (longitudinal / transverse) of the PBT materials prepared in Examples 1-3 and Comparative Examples 1-2 was determined according to the provisions of GB / T15585. The experimental results were statistically analyzed, and the quantitative data were used as... Mean ± standard deviation is expressed as mean ± standard deviation. The Kolmogorov-Smirnov test was used to test the normality of the data. For normally distributed data, the t-test was used to compare the differences in means between two groups, with P < 0.05 considered statistically significant. The results are shown in Table 1. Table 1 Note: * indicates that compared with Example 1 group, P<0.05.

[0046] The surface resistivity of the PBT materials prepared in Examples 1-3 and Comparative Examples 3-4 was determined according to GB / T 31838.3-2019 standard. Statistical analysis was performed on the experimental results, and the measurement data were used as... Mean ± standard deviation is expressed as mean ± standard deviation. The Kolmogorov-Smirnov test was used to test the normality of the data. For normally distributed data, the t-test was used to compare the differences in means between two groups, with P < 0.05 considered statistically significant. The results are shown in Table 2. Table 2 Note: * indicates that compared with Example 1 group, P<0.05.

[0047] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A low-shrinkage, antistatic PBT material for loose-sleeve tubing, characterized in that, It is made from the following components in parts by weight: 100-200 parts of polybutylene terephthalate, 30-50 parts of flame retardant, 0.5-1.5 parts of nucleating agent, 2-8 parts of antistatic agent, and 1-3 parts of lubricant.

2. The PBT material for low-shrinkage, antistatic loose-sleeve tubing according to claim 1, characterized in that, The viscosity of the polybutylene terephthalate is 0.75-0.

88.

3. The PBT material for low-shrinkage, antistatic loose-sleeve tubing according to claim 1, characterized in that, The flame retardant is one or more of aluminum hydroxide, zinc borate, ammonium polyphosphate, triphenyl phosphate, and melamine cyanurate.

4. The low-shrinkage, antistatic PBT material for loose-sleeve tubing according to claim 1, characterized in that, The nucleating agent is a mixture of bis[4-(1,1-dimethylethyl)benzoyl-oxy]aluminum hydroxide and polyvinylcyclopentane in a mass ratio of (1-3):

1.

5. The PBT material for low-shrinkage, antistatic loose-sleeve tubing according to claim 1, characterized in that, The antistatic agent is a mixture of methyltrihydroxyethylmethylammonium sulfate and nonionic antistatic agents in a mass ratio of 1:(1-3).

6. The PBT material for low-shrinkage, antistatic loose-sleeve tubing according to claim 5, characterized in that, The preparation method of the nonionic antistatic agent is as follows: pentaerythritol stearate and tristearate are put into a reaction vessel, nitrogen is introduced to control the negative pressure at 0.02-0.06 MPa, the temperature is raised to 120-140℃, and the reaction is carried out under stirring for 30-50 min, and then the temperature is lowered to 100-110℃ to obtain the nonionic antistatic agent; the weight ratio of tristearate to pentaerythritol stearate is (2-5):

1.

7. The PBT material for low-shrinkage, antistatic loose-sleeve tubing according to claim 1, characterized in that, The lubricant is one or more of stearic acid, calcium stearate, zinc stearate, and paraffin.

8. The method for preparing the low-shrinkage, antistatic PBT material for loose-sleeve tubing as described in claim 1, characterized in that, The following steps are followed: Polybutylene terephthalate, flame retardant, nucleating agent, antistatic agent, and lubricant are added to a high-speed mixer and mixed at a speed of 2500-3000 rpm / min for 5-10 minutes. After stirring evenly, the mixture is discharged to obtain a mixture. The mixture is then melted, extruded, and granulated through a twin-screw extruder to obtain PBT material.

9. The method for preparing the low-shrinkage, antistatic PBT material for loose-sleeve tubing according to claim 8, characterized in that, The parameters of the extrusion preparation process are as follows: screw speed: 50-100 r / min; temperature settings: first temperature zone: 170-190℃; second temperature zone: 200-210℃; third temperature zone: 210-220℃; fourth temperature zone: 200-210℃; fifth temperature zone: 190-200℃; sixth temperature zone: 190-200℃; die temperature: 220-240℃.